The Power of Electricity Leader's Guide - Sandra Fry; Lucinda Harris (EDIS)
The Power of Electricity Leader's Guide (4H EGL 40) is a leader-led project guide is for 4-H members ages 12-14. The Power of Electricity will help youth understand the environmental and economic issues associated with Electricity. The concepts learned are: understanding electricity, how electricity travels, electricity's silent partner, energy in action, and electric environment. The member's workbook (4H EGM 30) is used in conjunction with this publication. Printed June 1996. Reprinted October 1999. Reviewed June 2002.